Pemetaan Permukiman Kumuh Menggunakan Sistem Informasi Geografis (SIG) Di Kota Singaraja - Ni Putu Wira Kristyani; I Gede Yudi Wisnawa; I Gede Budiarta (Universitas Pendidikan Ganesha, 2023)
The issue of slums in urban areas is not easy to address, so it requires serious attention from the community and the Government. The development of a city is due to population growth, which increases the demand for land and consequently leads to the emergence of slums. Based on this, research is needed to assess the level of slums in Singaraja City. This study aims to map the level of slums in residential areas in Singaraja City and examine the impact of slum settlements on the Spatial Planning of Buleleng Regency. Data for this research were obtained through primary and secondary field surveys, and the data were analyzed using quantitative and qualitative analysis techniques. The findings of this study include a map of slum settlements in Singaraja City, providing information on the category of moderate slum levels in the Anyar Village District, mild slum levels in Kampung Baru Village, and areas outside these villages classified as non-slum settlements in Singaraja City. The impact of slum settlements on the spatial planning of Buleleng Regency is observed in the trade and services zone as well as the coastal border zone.